Does the type of cardioplegia used during valve surgery influence operative nadir hematocrit and transfusion requirements?. (November 2018) - Stammers, Alfred H.; Tesdahl, Eric A.; Mongero, Linda B.; Stasko, Andrew
Introduction: Myocardial protection is performed using diverse cardioplegic (CP) solutions with various combinations of chemical and blood constituents. Newer CP formulations that extend ischemic intervals may require greater asanguineous volume, contributing to hemodilution. Methods: We evaluated intraoperative hemodilution and red blood cell (RBC) transfusion rates among three common CP solutions during cardiac valve surgery. Data from 5, 830 adult cardiac primary valve procedures where either four-to-one blood CP (4:1), del Nido solution (DN) or microplegia (MP) was used at 173 United States surgical centers. The primary outcome was the nadir hematocrit (Hct) during cardiopulmonary bypass (CPB), with a secondary outcome of total units of RBC transfused intraoperatively. Outcomes were assessed using mixed-effects regression, with controls for patient size, age, first Hct in the operating room, ultrafiltration volume, net bypass circuit priming volume, anesthesia and perfusion asanguineous volumes, cross-clamp and total procedure times, procedure type, reoperation, hospital, surgeon and twelve other patient and procedural variables. Results: A total of 2, 641 patients received 4:1 (45.3%), 1, 864 received DN (32.0%) and 1, 325 received MP (22.7%). There were only slight differences in the central tendency (mean (SD)) for crude nadir Hct on CPB: 4:1, 25.5 (4.5), DN, 26.0 (4.6) and MP, 26.5 (4.7). After controlling for numerous operative and patient characteristics, the regression-adjusted estimate of the nadir Hct on CPB for MP was 26.2%, compared to 25.7% for 4:1 and 25.7% for DN; differences between MP and the other methods were statistically significant (p<0.01). Unadjusted mean RBC units transfused per patient was very similar across the groups (4:1, 2.2; MP, 2.3; DN, 2.4). Regression-adjusted estimates for the number of units of RBC transfused intraoperatively showed no statistically significant differences between CP methods. Conclusions: In patients undergoing cardiac valve surgery, the type of CP did not have a strong clinical impact on hemodilution or transfusion. Choice of a myocardial preservation solution can be made independently of its effect on intraoperative Hct.